Analisis perbandingan keputusan pembelian sepeda motor merek Honda Supra X 125R Dan Yamaha Jupiter MX 125 LC dari dimensi bauran pemasaran pada mahasiswa fakultas ekonomi Universitas Riau Pekanbaru - ', Adrian; ', Jushermi; ', Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to analyze and examine the difference of the purchase decision between the motorcycle Honda Supra X 125R with Yamaha Jupiter MX 125 LC on dimensions of marketing mix at Faculty of Economics’s students Riau University in Pekanbaru . Population in this research are Faculty of Economic’s students Riau University who owns the motorcycle Honda Supra X 125R and Yamaha Jupiter MX 125 LC. Sample derivation using purposive sampling. The number of sample are 100 peoples, that consist of 50 respondents who own the motorcycle Honda Supra X 125R, and 50 respondents who own the motorcycle Yamaha Jupiter MX 125 LC. The method of data analysis are using descriptive analysis and paired t-test. The results that showed in this research is, there are significant differences in purchase decision between the motorcycle Honda Supra X 125R and Yamaha Jupiter MX 125 LC on dimensions of marketing mix at Faculty of Economics’s students Riau University in Pekanbaru. The results showed that the value of purchase decision on dimensions of marketing mix is higher on the motorcycle Honda Supra X 125R compared with the motorcycle Yamaha Jupiter MX 125 LC, which promotion has the highest significant differences between them.Keywords : Marketing Mix, Purchase Decision